INCREASING THE EFFICIENCY OF SOLAR PANELS - Мережко, Юлія (SWorldJournal, 2024)
This article is dedicated to enhancing the efficiency of solar panels through technological solutions. The study aims to showcase technological solutions that improve the efficiency of solar panels. General scientific methods of cognition such as analysis